ADAPTASI BUDAYA DAN BENTURAN PERUNDANGAN-UNDANGAN: STUDI KASUS KOMUNITAS SAMIN DI KUDUS - Rosyid, Mohammad (Kebudayaan, 2017)
AbstractThis research was conducted to Samin community in Kudus Regency, Central Java Province. Data was obtainabled through interviews and observations to Wong Samin in Kudus, particularly at Lerakrejo Village, Kaliyoso sub-village, and Karangrowo Village, in Undaan district. This article is descriptive qualitative research. The purpose of this research is to know how adaption efforts that based on culture in Samin community, Kudus, when they are stigmatized by their surrounding communities, and modification of their teachings as a respon of dynamically. As a strategy for maintenance their identity, Wong Samin make notes in a book, which records of their identity and teachings in a simple way in an attempt to straighten out the negative stigma. The book also illustrates compliance teaching to the local government regulations, such as formal school, pay taxes, active in election, and registration of marriages. Wong Samin also assimilate with non-Samin and accommodate non-Samin culture in their environment. Their efforts bring in a positively respon from surrounding community. As an evidence, a part of them is inducted as a chairman of neighborhood association (RT), surrounding association (RW), and farmer groups. However, the main problem that must be faced of Samin community in Kudus is their paddy field as their source economy often failed. So, they are to be urban workers in many cities. The impacts are, homeschooling and pirukunan (gemeinschaft) not repeated agen, because their elders and adult generation to be migrants and returning home uncertainly. Their routine social activities with non-Samin community in their residents are not maximal also.AbstrakRiset ini dilakukan pada komunitas Samin di Kabupaten Kudus, Provinsi Jawa Tengah. Data diperoleh dengan wawancara dan observasi dengan wong Samin Kudus, khususnya di Desa Larekrejo dan Dusun Kaliyoso, Desa Karangrowo, Kecamatan Undaan. Analisis riset ini deskriptif kualitatif. Tujuan riset ini adalah untuk mengetahui bagaimana upaya adaptasi berbasis budaya yang dilakukan komunitas Samin di Kudus tatkala distigma lingkungannya dan mengalami pergeseran atas ajarannya akibat dinamika masa kini yang diresponnya. Strategi dalam mempertahankan jati dirinya, wong Samin membuat catatan yang dibukukan berupa jati diri dan ajarannya dalam bentuk sederhana sebagai upaya meluruskan stigma. Di dalamnya juga menggambarkan ketaatannya pada peraturan pemerintah seperti sekolah formal, membayar pajak, aktif dalam pemilu, selain pencatatan perkawinan, membaur dengan warga non-Samin, dan mengakomodasi budaya non-Samin di lingkungannya. Upaya tersebut membuahkan hasil yakni direspon positif lingkungannya dengan bukti dipercaya sebagai Ketua RT, RW, dan kelompok tani. Akan tetapi, problem utama yang dihadapi komunitas Samin di Kudus adalah sumber perekonomiannya sebagai petani padi yang mengalami kegagalan sehingga menjadi pekerja urban di kota. Imbasnya, homeschooling dan pertemuan pirukunan tak lagi berlangsung karena sesepuh dan generasi dewasa menjadi perantau yang pulangnya tak menentu. Rutinitas kegiatan sosial kemasyarakatan dengan warga non-Samin di lingkungannya pun tak maksimal.Â